Blockchain Enabled Vehicular Communications: Fad or Future? - Bartolomeu, Paulo C. (2020)
This paper discusses the application of the blockchain technology to wireless communications, in particular, for enhancing the security of vehicular communications. The idea that the blockchain will become a key solution for ensuring security and data consistency has long been controversial, even in more traditional areas such as finance or real-estate, for example. In this paper, an analysis of the two opposing sides is put forward and a review of the key aspects that need further evolution to ensure the blockchain's survival is presented. In the context of vehicular communications existing blockchain applications are examined with focus on certificate and reputation management, and message forwarding promotion. In this scope, the future of the blockchain is debated with emphasis on the key limitations of public implementations.